2015
DOI: 10.1074/jbc.m115.642835
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Efflux Propensity Is the Key Determinant of Ca2+-independent Phospholipase A-β (iPLAβ)-mediated Glycerophospholipid Hydrolysis

Abstract: Background: Ca 2ϩ -independent phospholipase A-␤ (iPLA␤) has been repeatedly implicated as a homeostatic enzyme. Results: Activity of iPLA␤ correlates inversely with the hydrophobicity of the phospholipid substrate. Conclusion: Efflux of the phospholipid substrate from a membrane mainly determines the activity of iPLA␤. Significance: Results support the role of iPLA␤ as a homeostatic enzyme that responds to increased phospholipid efflux proposed to occur at particular "critical" compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
(71 reference statements)
5
10
0
Order By: Relevance
“…Consistently, we have recently shown that PNPLA9, -6 and -4 catalyze homeostatic degradation of PC, PE and PS in human cells (26). More importantly, we have provided strong evidence that the activity of PNPLA9 in vitro is proportional to the propensity of its GPL substrate to efflux from the membrane (27), consistent with the prediction that the active site of PNPLA9 resides well above the membrane surface (28). Since the efflux propensity of a GPL molecule should be proportional to its chemical activity, we propose that homeostatic degradation of GPLs in mammalian cells depends on their chemical activity.…”
Section: Increased Chemical Activity Renders Gpls Susceptible To Hydrsupporting
confidence: 83%
“…Consistently, we have recently shown that PNPLA9, -6 and -4 catalyze homeostatic degradation of PC, PE and PS in human cells (26). More importantly, we have provided strong evidence that the activity of PNPLA9 in vitro is proportional to the propensity of its GPL substrate to efflux from the membrane (27), consistent with the prediction that the active site of PNPLA9 resides well above the membrane surface (28). Since the efflux propensity of a GPL molecule should be proportional to its chemical activity, we propose that homeostatic degradation of GPLs in mammalian cells depends on their chemical activity.…”
Section: Increased Chemical Activity Renders Gpls Susceptible To Hydrsupporting
confidence: 83%
“…Consistently, we have recently shown that PNPLA9, −6, and −4 catalyze homeostatic degradation of PC, PE, and PS in human cells . More importantly, we have provided strong evidence that the activity of PNPLA9 in vitro is proportional to the propensity of its GPL substrate to efflux from the membrane to the active site of PNPLA9, predicted to reside well above the membrane surface . Since the efflux propensity of a GPL molecule should be proportional to its chemical activity, we propose that the rate of homeostatic degradation of GPLs correlates positively on their chemical activity.…”
Section: Introductionsupporting
confidence: 82%
“…The phospholipase substrate preferences partly arise from the placement of the PUFA precursors in different molecular species of membrane GPLs. In addition to the reported preferences to hydrolyze a specific sn-2 acyl chain (e.g., 20:4n-6 by cPLA 2 IV), the sn-1 acyl chain also affects the rate of GPL species hydrolysis due to the different degree of hydrophilicities and efflux propensities of different GPL species from the membrane bilayer (66)(67)(68). Functional consequences follow since Dong et al (51) found that the coadministered nonessential fatty acids, 16:0, 18:1n-9, and 18:0 stimulated 20:4n-6-derived COX-2 activity, and the highest stimulation was recorded with the combination 16:0/20:4n-6, which species was kept as a minor component of the PC and PE of hBMSCs.…”
Section: Discussionmentioning
confidence: 99%